2017
DOI: 10.1111/inr.12378
|View full text |Cite
|
Sign up to set email alerts
|

Association between fear of childbirth and maternal acceptance of pregnancy

Abstract: The results from this study can be used to help: increase awareness among health professionals (doctors, nurses, midwives) in antenatal care services about a mother's adaptation to pregnancy and the negative effects of fear of childbirth; direct future research examining factors affecting adaptation to pregnancy and fear of childbirth; establish routine assessments for adaptation to pregnancy and fear of childbirth; provide professional support for women with difficulties adapting to pregnancy and with fear of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 42 publications
2
17
0
5
Order By: Relevance
“…We used the CAQ to assess the FOC in repregnant women after CS in China. The total CAQ score in our study was 43.76, which was close to that in a study conducted in Turkey [26] and higher than those in studies conducted in the U.S. (31.70) and Greece (31.22) [22,27]. This result indicated that repregnant women after CS in China might have the same moderate FOC as do women in Turkey, which was higher than that of pregnant women in the U.S. and Greece.…”
Section: Discussionsupporting
confidence: 87%
“…We used the CAQ to assess the FOC in repregnant women after CS in China. The total CAQ score in our study was 43.76, which was close to that in a study conducted in Turkey [26] and higher than those in studies conducted in the U.S. (31.70) and Greece (31.22) [22,27]. This result indicated that repregnant women after CS in China might have the same moderate FOC as do women in Turkey, which was higher than that of pregnant women in the U.S. and Greece.…”
Section: Discussionsupporting
confidence: 87%
“…N. Aksoy et al, 2015; M. Aksoy, Aksoy, Dostbil, Celik, & Ince, 2014; Coşkuner Potur, Mamuk, Şahin, Demirci, & Hamlaci, 2017; Erkaya, Karabulutlu, & Çalık, 2017; Güleç, Öztürk, Sevil, & Kazandi, 2014; İsbir et al, 2016; Karabulut et al, 2016; Kızılırmak & Başer, 2016; Körükcü, Deliktaş, Aydın, & Kabukcuoğlu, 2017; Okumus & Şahin, 2017; Şahin, Dinç, & İşsiz, 2009; Serçekuş & Başkale, 2016).…”
Section: Resultsunclassified
“…Potur ve ark. 'nın (12) gebeliğin kabulü ve doğum korkusu arasındaki ilişkiyi inceledikleri çalışmada, gebeliğin kabulünün orta düzeyde olduğu saptanmıştır. Karabulut ve ark.…”
Section: Verilerin Toplanmasıunclassified